Education as the engine of development in South Korea. Teachings for Colombia (2013)
One of the biggest concerns in Colombia, at the social level, is the poor quality of its educational model and the high drop-out rates, which has led it to occupy one of the lowest positions worldwide in terms of education. Therefore, if Colombia wants to bet on greater academic competitiveness, it should take as an example the teachings of world leaders on the subject. This article analyzes the case of South Korea as the best country in academic performance worldwide, and the possible applications of its system in Colombia.